Qualidade física e sensorial de coffea canephora L. relacionadas á altitude, estádio de maturação e preparo pós-colheita - Sturm, Gustavo Martins (2012)
The quality of conilon coffee (Coffea canephora) is a much broached theme at present, and this quality is much variable and may be influenced by many factors. This way, this work had as objective to evaluate the influence of altitude, the maturation stage